EDUCATIONAL MANAGEMENT GRADUATES’ PERSONAL QUALITIES, WORK VALUES AND JOB PERFORMANCE: THE RELATED LEARNING EXPERIENCE (RLE) MODEL - Hilarion A. Odivilas; Florita O. Odivilas (European Scientific Journal, ESJ, 2015)
This study evaluated the personal qualities, work values and job performance of graduates using the descriptive correlation method employing self-structured questionnaires. The results of the study revealed that the personal qualities of graduates in terms of personal character, initiative and personality were found to be very good. The work values of the graduates such as work ethics, diligence, teamwork and creativity were rated “practiced” by the respondents. However, motivation, self-confidence and professionalism were rated “moderately practiced” by the supervisors but graded “practiced” by the graduates themselves. The difference in work values of diligence, self-motivation, creativity, self-confidence and professionalism were rated significant except for work ethics and creativity. The graduate respondents’ performance rating for the School Year 2010- 2011 reached a mean of 4.19 or very satisfactory. The relationship between personal qualities in terms of personal character, initiative and personality and job performance were not significant. Similarly, the relationship between work values in terms of work ethics, diligence, teamwork, selfmotivation, creativity and professionalism and job performance were not significant, except for self-confidence.